Ethnomedicinal and Traditional uses of the Flora of District Lower Dir, Khyber Pakhtunkhwa, Pakistan - Irfan, Muhammad; Ullah, Fazal; Haq, Inzimam Ul (Ethnobotany Research and Applications, 2023)
Background: The present study aimed to assess the traditional knowledge and uses of ethnomedicinal plants to cure different disorders. The local inhabitants of district Lower Dir, Pakistan was relied on medicinal plants for their fundamental medical requirements. Methods: The ethnomedicinal and traditional knowledge was approached by using the questionnaire and random interviews. Mostly old people were approached for the collection of information regarding the traditional uses of medicinal plant. The data were analyzed with the help of various statistical indices such as fidelity level (FL), use value (UV), relative popularity level (RPL), relative order priority (ROP), relative frequency citation (RFC) and jaccard index (JI). Results: A total of 147 taxa belonged to 106 genera and 57 families were reported. The dominant family was Lamiaceae with 18 taxa (12.24%), Asteraceae was the second largest family with 12 taxa (8.16%), Rosaceae was the third largest family with 9 taxa (6.12%), Solanaceae and Brassicaceae with 6 taxa each (8.16%), Amarantheaceae, Brassicaceae, Berberidaceae and Rutaceae with 5 taxa each (13.6%), Violaceae with 4 taxa (2.72%), Apiaceae, Apocynaceae, Cucurbitaceae, Euphorbiaceace, Plantaginaceae, Polygonaceae, and Ranunculaceace with 3 taxa each (14.28%), followed by Acanthaceae, Amaryllidaceae, Fagaceae, Mimosaceae, Moraceae, Myrtaceae, Pinnaceae, Rhamnaceae, Saxifragaceae, Scrophulariacea, Thymelaeaceae, and Verbrnaceae with 2 taxa each (16.32%), while the remaining families contained one taxon each (18.4%). Regarding the parts used mostly leaves of 67 taxa (45.57%), followed by fruits of 25 taxa (17%), roots of 20 taxa (13.60%), seeds of 11 taxa (7.48%), whole plant of 9 taxa (6.12%), bark of 7 taxa (4.76%), oils extracted from seeds and gums of 4 taxa each (5.44%) were used. Conclusion: The current study provided useful knowledge about ancient using of therapeutic plants species that were utilized by the local inhabitants for curving of various disorders. The inhabitants of the area have diverse knowledge about the remedies of medication for effective work against ailments. Keywords: Ethnomedicine, Fidelity level, Jaccard index, Lower Dir, Pakistan, Use value.